Biology and evolution of the mollusca. Volume 1 - Ponder, W. F.; Lindberg, David R., 1948-; Ponder, Juliet Mary (Boca Raton, FL : CRC Press, 2020)
Molluscs comprise the second largest phylum of animals (after arthropods), occurring in virtually all habitats. Some are commercially important, a few are pests and some carry diseases, while many non-marine molluscs are threatened by human impacts which have resulted in more extinctions than all tetrapod vertebrates combined. This book and its companion volume provide the first comprehensive account of the Mollusca in decades. Illustrated with hundreds of colour figures, it reviews molluscan biology, genomics, anatomy, physiology, fossil history, phylogeny and classification. This volume includes general chapters drawn from extensive and diverse literature on the anatomy and physiology of their structure, movement, reproduction, feeding, digestion, excretion, respiration, nervous system and sense organs. Other chapters review the natural history (including ecology) of molluscs, their interactions with humans, and assess research on the group. Key features of both volumes: up to date treatment with an extensive bibliography; thoroughly examines the current understanding of molluscan anatomy, physiology and development; reviews fossil history and phylogenetics; overviews ecology and economic values; and summarises research activity and suggests future directions for investigation. Winston F Ponder was a Principal Research Scientist at The Australian Museum in Sydney where he is currently a Research Fellow. He has published extensively over the last 55 years on the systematics, evolution, biology and conservation of marine and freshwater molluscs, as well as supervised post graduate students and run university courses. David R. Lindberg is former Chair of the Department of Integrative Biology, Director of the Museum of Paleontology, and Chair of the Berkeley Natural History Museums, all at the University of California. He has conducted research on the evolutionary history of marine organisms and their habitats on the rocky shores of the Pacific Rim for more than 40 years. The numerous elegant and interpretive illustrations were produced by Juliet Ponder.
OCLC-licensed vendor bibliographic record.
Keywords: Mollusks; Mollusks -- Evolution; NATURE / Animals; SCIENCE / Life Sciences / Evolution; SCIENCE / Life Sciences / Biology / Marine Biology